UV-curable antistatic coating as well as preparation method and use method thereof
By adding modified antistatic agents to the surface of polymer materials and using UV curing technology, the problems of electrostatic accumulation and high-temperature curing are solved, and the antistatic effect is achieved lasting and stable, reducing cost and manufacturing difficulty.
Patent Information
- Application Number
- CN202411911546.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-29
AI Technical Summary
Due to the insulating properties of existing polymer materials, static electricity is difficult to effectively dissipate on their surface, resulting in static electricity accumulation may cause equipment malfunction, fire or explosion. In addition, existing antistatic coatings are difficult to cure or manufacture at high temperatures, are costly, and their conductivity is easily affected by environmental factors.
By adding modified antistatic agents to the coating itself, using conductive particles to create charge transport channels to achieve rapid dispersion of static electricity; UV curing is used to cure the coating to avoid thermal deformation caused by high temperature and increase solvent usage.
The antistatic effect is achieved lasting and stable, reducing the risk of electrostatic accumulation on the coating surface, simplifying the preparation process, reducing costs, and reducing the damage to the substrate by high temperatures.
Smart Images

Figure BDA0005205804040000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, and in particular to a UV curing antistatic coating and a preparation method and a use method thereof. Background Art
[0002] In today's society, polymer materials have become a key driving force for promoting scientific and technological progress and industrial upgrading with their excellent performance and wide application. Polymer materials are used in fields such as high-performance engineering plastics and resin materials for copper-clad laminates, core components of 5G communications, supporting the construction and development of infrastructure in the information age. However, since most polymer materials have excellent insulation properties, static electricity is difficult to dissipate effectively on their surfaces. Once accumulated to a critical point, it can cause equipment malfunctions at best, or even cause fires or explosions at worst. Therefore, it is crucial to drain static electricity from the surface of polymer materials.
[0003] In the prior art, some researchers have prepared transparent antistatic coatings with PEDOT / PSS as the antistatic main material by using crosslinking agent pre-hydrolysis as a precursor for the hydrolysis of tetraalkoxy compounds, but it needs to be thermally cured at a high temperature above 200°C, so it cannot meet the needs of some precision instruments and large facilities. In response to this, some researchers have proposed adding photoinitiators to certain polymers that are conductive in themselves and curing them through UV to form a film. The base material of the coating itself can conduct electricity and does not need to add other conductive materials, but its manufacturing and processing are difficult and expensive, which limits its wide application. At the same time, its conductivity will also be affected by environmental factors, such as temperature, humidity, etc., which may affect the stability of its antistatic performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a UV curing antistatic coating and its preparation method and use method. The present invention uses the coating itself as a matrix, and produces an antistatic effect by adding a modified antistatic agent, and the antistatic effect is more durable and stable; at the same time, the present invention cures the coating by UV curing. Compared with the traditional thermal curing method, UV curing has the advantages of fast curing speed, simple equipment, and small amount of solvent. In addition, since UV curing does not generate heat, it will not cause thermal deformation of the coating and the substrate. It can be widely used in the construction of surface coatings of heat-sensitive substrates to reduce the damage of high temperature to the substrate.
[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a UV curing antistatic coating, comprising the following raw materials in parts by weight: 85-95 parts of a resin matrix, 1-10 parts of an antistatic agent, and 3-5 parts of a photoinitiator.
[0006] Compared with the method of adding an antistatic layer on the surface of the coating, the present invention uses the coating itself as the matrix, and by adding an antistatic agent, the coating itself produces an antistatic effect. The antistatic agent can create a charge transfer channel through conductive particles, so that static electricity can be quickly dispersed instead of being concentrated in a certain area, preventing static electricity accumulation and protecting sensitive components from static electricity damage. This method can effectively reduce the accumulation of static electricity on the surface of the coating, and the preparation process is simpler and cheaper than that of intrinsic antistatic coatings. In addition, the present invention cures the coating by UV curing. Compared with traditional thermal curing methods, UV curing has the advantages of fast curing speed, simple equipment, and small amount of solvent; at the same time, since the UV curing process does not generate heat, it will not cause thermal deformation of the coating and the substrate, and can be widely used in the construction of surface coatings of heat-sensitive substrates, reducing the damage of high temperature to the substrate and reducing the emission of organic solvents.
[0007] Wherein: in the coating of the present invention, the resin matrix comprises the following raw materials in parts by weight: 30-40 parts of maleic anhydride, 30-40 parts of tetrahydrophthalic anhydride, 12-17 parts of ethylene glycol, 15-20 parts of propylene glycol, 3-5 parts of diluent, 0.5-2 parts of inhibitor, and 1-3 parts of production aid.
[0008] The present invention uses the hydroxyl group in the polyol as a nucleophilic reagent to perform nucleophilic attack on the carbonyl group of the acid anhydride to form an unstable six-membered ring transition state, and the six-membered ring transition state is rearranged to release a molecule of water to form an ester bond, and then the reaction is repeated to form a polymer, which is then capped with an inhibitor, a diluent is added to adjust the viscosity, and finally a production aid is added. The resin matrix can be obtained by cooling.
[0009] Preferably, the antistatic agent includes one or more of hydroxyl-modified carbon nanotubes, silver-carbon nanotubes (carbon nanotubes with silver element grafted on the surface) and copper powder.
[0010] The antistatic agents used in the present invention are all modified conductive fillers, which have better conductive effects than ordinary conductive fillers; at the same time, introducing functional groups into the conductive fillers can cause bonding reactions between them and resin groups, which are more unbreakable than traditional physical attachment, so that the coating has long-lasting and stable antistatic properties.
[0011] Preferably, the diluent is selected from styrene and methacrylate fatty acid; the inhibitor is selected from methylhydroquinone, para-benzoquinone and hydroquinone; the production aid includes a leveling agent and / or a defoaming agent, wherein the leveling agent is selected from BYK-310, 301, 306, 307 and the like; the defoaming agent is selected from BYK555, SF809B and the like.
[0012] Preferably, the photoinitiator is selected from Irgacure series photoinitiators, such as Irgacure1173, IrgacureTPO, and Irgacure819.
[0013] In a second aspect, the present invention provides a method for preparing a UV-curing antistatic coating, which comprises the following steps: adding an antistatic agent to a resin matrix, mixing uniformly, adding a photoinitiator, and mixing uniformly to obtain a UV-curing antistatic coating.
[0014] Preferably, the preparation method of the resin matrix comprises: mixing ethylene glycol and propylene glycol uniformly, heating to 55-65°C, adding maleic anhydride, heating to 110-130°C to melt it, adding tetrahydrophthalic anhydride, continuing to heat to 170-190°C and keeping it warm for 1-3h, the maximum temperature during the initial insulation period does not exceed 200°C, otherwise it may cause the volatilization of alcohol not participating in the reaction, and then heating to 195-210°C and keeping it warm for 0.5-2h to improve the monomer conversion rate and promote the trend of resin conversion to high molecular weight, then cooling to 160-180°C, adding an inhibitor, too low temperature will affect the effect of the inhibitor, and then cooling to 110-130°C, adding a diluent and a production aid, during which the temperature is too low, the resin viscosity will increase, affecting the uniform mixing of the diluent and the production aid, and finally cooling to about 50°C for discharge to obtain a resin matrix.
[0015] Preferably, the preparation method of the hydroxyl-modified carbon nanotubes comprises: adding 2-5 parts by weight of carbon nanotubes to 95-98 parts by weight of an acid-modified solution, stirring the reaction for 5-6 hours, and then ultrasonically dispersing at 60-70° C. for 15-25 hours, at which time the side walls and the beginnings of the carbon nanotubes will be oxidized by the acid-modified solution, and then connected with hydroxyl groups to obtain hydroxyl-modified carbon nanotubes.
[0016] More preferably, the carbon nanotubes have a diameter of 60-80 nm and a length of 20-40 μm; and the acid-modified solution is concentrated nitric acid, concentrated sulfuric acid or nitrous acid.
[0017] Preferably, the preparation method of the silver-carbon nanotubes comprises: adding 0.3-1 parts by weight of carbon nanotubes to 20-40 parts by weight of a composite strong oxidizing solution, stirring and reacting at 85-95° C. for 1-2 hours, washing, filtering, drying and grinding after the reaction is completed, which is a pretreatment stage of the carbon nanotubes, removing impurities and oxides on the surface thereof, and providing a highly active surface for subsequent adsorption; then adding 25-45 parts by weight of a composite modified solution, stirring and reacting at room temperature for 2-3 hours, washing, filtering, drying and grinding after the reaction is completed, which step will form nanoparticles on the surface of the carbon nanotubes as seeds for the catalytic center of the subsequent silver precipitation; then placing it in 25-35 parts by weight of a silver ammonia solution and stirring and reacting for 0.5-1 hour, adding 3-7 parts by weight of glucose and continuing to stir and react for 2-3 hours, the silver ammonia solution in this step provides a source of silver ions and reduction conditions, so that the silver ions are reduced to silver on the surface of the carbon nanotubes, and washing, filtering, drying and grinding after the reaction is completed to obtain silver-carbon nanotubes.
[0018] Further preferably, the composite strong oxidizing solution is a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of (1.5-2.5):1; the composite modified solution is a mixed solution of stannous chloride solution and concentrated hydrochloric acid in a mass ratio of (0.5-1.5):1; the concentration of the stannous chloride solution is 0.3-0.7 g / L; the silver ammonia solution is ammonia water containing 3-7wt% silver nitrate.
[0019] More preferably, the carbon nanotubes have a diameter of 60-80 nm and a length of 20-40 μm.
[0020] Preferably, the copper powder is pretreated: 20-25 parts by weight of copper powder is added to 35-55 parts by weight of a modified solution, and the mixture is stirred for reaction for 1-2 hours. This step allows the cupric oxide and cuprous oxide in the copper powder to react with concentrated hydrochloric acid to generate cupric chloride and cuprous chloride, wherein cupric chloride can be dissolved in water, and cuprous chloride has a low solubility, but ethanol in the solution can form a complex with the cuprous chloride to prevent its precipitation. After filtering, the mixture is added to 40-55 parts by weight of a purified solution and stirred for 10-20 minutes. This step can completely wash away impurities remaining on the copper powder, and the mixture is dried after filtering to obtain pretreated copper powder.
[0021] More preferably, the modified solution is a mixed solution of anhydrous ethanol and concentrated hydrochloric acid in a mass ratio of (0.5-1.5) : 1.
[0022] More preferably, the purification solution is ether, anhydrous ethanol or isopropanol.
[0023] In a third aspect, the present invention provides a method for using a UV-curable antistatic coating, comprising: applying the UV-curable antistatic coating on the surface of a substrate, and UV curing for 1-5 minutes to obtain a UV-curable antistatic coating.
[0024] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention uses the coating itself as the matrix and produces an antistatic effect by adding a modified antistatic agent, which can prevent static electricity from accumulating on the coating surface and protect sensitive parts from static damage. In addition, the antistatic agent of the present invention is modified to react with the matrix resin group, and the antistatic effect is more durable and stable compared to the traditional physical attachment method.
[0025] (2) The present invention cures the coating by UV curing. Compared with the traditional thermal curing method, UV curing has the advantages of fast curing speed, simple equipment, and small amount of solvent. In addition, since UV curing does not generate heat, it will not cause thermal deformation of the coating and the substrate. It can be widely used in the construction of surface coatings of heat-sensitive substrates to reduce the damage of high temperature to the substrate. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with the embodiments.
[0027] Overall embodiment First, a UV curing antistatic coating comprises the following raw materials in parts by weight: 85-95 parts of a resin matrix, 1-10 parts of an antistatic agent, and 3-5 parts of a photoinitiator. Among them: The resin matrix comprises the following raw materials in parts by weight: 30-40 parts of maleic anhydride, 30-40 parts of tetrahydrophthalic anhydride, 12-17 parts of ethylene glycol, 15-20 parts of propylene glycol, 3-5 parts of diluent, 0.5-2 parts of inhibitor, and 1-3 parts of production aid.
[0028] In some preferred implementation cases, the diluent is selected from styrene, methacrylate fatty acid; the inhibitor is selected from methylhydroquinone, para-benzoquinone, and hydroquinone; the production aid includes a leveling agent and / or a defoaming agent; wherein, in some more preferred implementation cases, the leveling agent is selected from BYK-310, 301, 306, 307, etc.; the defoaming agent is selected from BYK555, SF809B, etc.
[0029] The antistatic agent includes one or more of hydroxyl-modified carbon nanotubes, silver-carbon nanotubes and copper powder.
[0030] In some preferred implementation cases, the photoinitiator is selected from Irgacure series photoinitiators, such as Irgacure1173, Irgacure TPO, and Irgacure819.
[0031] Secondly, a method for preparing a UV-curing antistatic coating comprises the following steps: adding an antistatic agent to a resin matrix, mixing uniformly, adding a photoinitiator, and mixing uniformly to obtain a UV-curing antistatic coating.
[0032] In some preferred implementation cases, as a preferred method, the preparation method of the resin matrix includes: mixing ethylene glycol and propylene glycol evenly, heating to 55-65°C, adding maleic anhydride, heating to 110-130°C to melt it, then adding tetrahydrophthalic anhydride, continuing to heat to 170-190°C and keeping warm for 1-3h, the maximum temperature during the initial insulation period does not exceed 200°C, otherwise it may cause volatilization of alcohol not participating in the reaction, and then heating to 195-210°C and keeping warm for 0.5-2h to improve the monomer conversion rate and promote the trend of resin conversion to a large molecular weight, then cooling to 160-180°C, adding an inhibitor, too low temperature will affect the effect of the inhibitor, and then cooling to 110-130°C, adding a diluent and a production aid, during which the temperature is too low, the resin viscosity will increase, affecting the uniform mixing of the diluent and the production aid, and finally cooling to about 50°C for discharge to obtain a resin matrix.
[0033] In some preferred implementation cases, the preparation method of the hydroxyl-modified carbon nanotubes includes: adding 2-5 parts by weight of carbon nanotubes to 95-98 parts by weight of an acid-modified solution, stirring the reaction for 5-6 hours, and then ultrasonically dispersing at 60-70°C for 15-25 hours. At this time, the side walls and the beginnings of the carbon nanotubes will be oxidized by the acid-modified solution, and then hydroxyl groups will be connected to obtain hydroxyl-modified carbon nanotubes.
[0034] In some more preferred implementation cases, the diameter of the carbon nanotubes is 60-80 nm, and the length of the carbon nanotubes is 20-40 μm; and the acid-modified solution is concentrated nitric acid, concentrated sulfuric acid or nitrous acid.
[0035] In some preferred implementation cases, the preparation method of the silver-carbon nanotubes includes: adding 0.3-1 parts by weight of carbon nanotubes to 20-40 parts by weight of a composite strong oxidizing solution, stirring and reacting at 85-95°C for 1-2 hours, washing, filtering, drying and grinding after the reaction is completed. This step is the pretreatment stage of the carbon nanotubes, removing impurities and oxides on the surface thereof, and providing a highly active surface for subsequent adsorption; then adding 25-45 parts by weight of a composite modified solution, stirring and reacting at room temperature for 2-3 hours, washing, filtering, drying and grinding after the reaction is completed. This step will use nanoparticles on the surface of the carbon nanotubes as seeds for the catalytic center of the subsequent silver precipitation; then placing it in 25-35 parts by weight of a silver ammonia solution and stirring and reacting for 0.5-1 hour, adding 3-7 parts by weight of glucose and continuing to stir and react for 2-3 hours. The silver ammonia solution in this step provides a source of silver ions and reduction conditions, so that the silver ions are reduced to silver on the surface of the carbon nanotubes. After the reaction is completed, washing, filtering, drying and grinding are performed to obtain silver-carbon nanotubes.
[0036] In some more preferred implementation cases, the composite strong oxidizing solution is a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of (1.5-2.5) : 1.
[0037] In some more preferred implementation cases, the composite modified solution is a mixed solution of stannous chloride solution and concentrated hydrochloric acid in a mass ratio of (0.5-1.5):1; the concentration of the stannous chloride solution is 0.3-0.7 g / L.
[0038] In some more preferred implementation cases, the silver ammonia solution is ammonia water containing 3-7wt% silver nitrate.
[0039] In some more preferred implementation cases, the carbon nanotubes have a diameter of 60-80 nm and a length of 20-40 μm.
[0040] In some preferred implementation cases, the copper powder is pretreated: 20-25 parts by weight of copper powder is added to 35-55 parts by weight of the modified solution, and the reaction is stirred for 1-2 hours. This step can make the cupric oxide and cuprous oxide in the copper powder react with concentrated hydrochloric acid to generate cupric chloride and cuprous chloride, wherein cupric chloride can be dissolved in water, and cuprous chloride has a low solubility, but the ethanol in the solution can form a complex with it to prevent its precipitation. After filtering, it is added to 40-55 parts by weight of the purified solution and stirred for 10-20 minutes. This step can completely wash away the impurities remaining on the copper powder, and after filtering, it is dried to obtain the pretreated copper powder.
[0041] In some more preferred implementation cases, the modified solution is a mixed solution of anhydrous ethanol and concentrated hydrochloric acid in a mass ratio of (0.5-1.5) : 1.
[0042] In some more preferred implementation cases, the purification solution is ether, anhydrous ethanol or isopropanol.
[0043] Finally, a method for using a UV curing antistatic coating comprises: applying the UV curing antistatic coating on the surface of a substrate, UV curing, and obtaining a UV curing antistatic coating.
[0044] In some preferred implementation cases, the UV curing time is 1-5 minutes.
[0045] Specific Examples and Comparative Examples Resin matrix preparation example: Example 1 Pour 16.5g ethylene glycol and 19.6g propylene glycol into a four-necked flask, set the speed to 100rpm and start stirring, raise the temperature to 60℃, add 17g maleic anhydride, continue to raise the temperature to 120℃ and add 39.2g tetrahydrophthalic anhydride. Raise the temperature to 180℃ and keep it for 2 hours, then gradually raise the temperature to 200℃, keep it for 1h, cool it down to 170℃ and add 1.6g methylhydroquinone, continue to cool it down to 120℃ and add 5.5g styrene, and finally add 0.5g BYK-301 defoamer and 1.4g BYK555 leveling agent to obtain a resin matrix.
[0046] Example 2 16.5g of ethylene glycol and 19.6g of propylene glycol were poured into a four-necked flask, the speed was set to 100rpm and stirring was started, the temperature was raised to 60°C, 17g of maleic anhydride was added, the temperature was continued to rise to 120°C and 39.2g of tetrahydrophthalic anhydride was added. The temperature was raised to 180°C and kept for 1 hour, then gradually raised to 200°C and kept for 0.5h, the temperature was lowered to 170°C and 1.6g of methylhydroquinone was added, the temperature was continued to fall to 120°C and 5.5g of styrene was added, and finally 0.5g of BYK-301 defoamer and 1.4g of BYK555 leveling agent were added to obtain a resin matrix (shortened reaction time group).
[0047] Preparation example of antistatic agent: Example 3 (Silver-Carbon Nanotubes) Pour 0.5g of carbon nanotubes into 30g of a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 2:1, stir at a speed of 80rpm for 2h at 90°C, and wash, filter, dry and grind into powder repeatedly with a large amount of distilled water after the reaction is completed. Then pour the powder into 30g of a mixed solution of stannous chloride solution (0.5g / L) and concentrated hydrochloric acid in a mass ratio of 1:1, stir at room temperature for 3h, and wash, filter, dry and grind into powder repeatedly with a large amount of distilled water after the reaction is completed. Then put it into 35g of a silver ammonia solution with a mass fraction of 5%, stir at a speed of 100rpm for 1h at room temperature, then add 5g of glucose and continue stirring for 2h, and wash, filter, dry and grind into powder repeatedly with a large amount of distilled water after the reaction is completed to obtain silver-carbon nanotubes.
[0048] Example 4 (Hydroxy-modified carbon nanotubes) 2 g of carbon nanotubes were poured into 98 g of concentrated nitric acid, stirred at 80 rpm for 5 h at room temperature, and then ultrasonically dispersed at 65° C. for 20 h to connect hydroxyl groups to the surface of the carbon nanotubes, thereby obtaining hydroxyl-modified carbon nanotubes.
[0049] Embodiment 5 (pretreatment copper powder) Pour 22g of copper powder into 40g of a mixed solution of anhydrous ethanol and concentrated hydrochloric acid in a mass ratio of 1:1, stir at 80rpm for 1.5h at room temperature, filter, pour the copper powder into 40g of anhydrous ethanol, stir at 180rpm for 20min, filter, and dry in a vacuum oven to obtain pretreated copper powder.
[0050] Coating preparation example: Example 6 7 g of the silver-carbon nanotubes prepared in Example 3 were added to 90 g of the resin matrix prepared in Example 1, and then 3 g of Irgacure 819 were added, and the mixture was uniformly mixed by stirring and ultrasonication to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in an ultraviolet light curing machine for 5 minutes to obtain a UV-curable antistatic coating.
[0051] Example 7 The only difference from Example 6 is that the amount of silver-carbon nanotubes added is reduced from 7 g to 4 g, and the remaining steps, materials and composition are consistent with Example 6, specifically including: 4 g of the silver-carbon nanotubes prepared in Example 3 were added to 90 g of the resin matrix prepared in Example 1, and then 3 g of Irgacure 819 was added, and the mixture was uniformly mixed by stirring and ultrasonication to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in a UV curing machine for 5 minutes to obtain a UV-curable antistatic coating.
[0052] Example 8 The only difference from Example 6 is that the amount of silver-carbon nanotubes added is increased from 7 g to 10 g, and the remaining steps, materials and composition are consistent with Example 6, specifically including: 10g of the silver-carbon nanotubes prepared in Example 3 were added to 90g of the resin matrix prepared in Example 1, and then 3g of Irgacure 819 was added, and ultrasonic stirring was performed to uniformly mix the mixture to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in a UV curing machine for 5 minutes to obtain a UV-curable antistatic coating.
[0053] Example 9 The only difference from Example 6 is that the silver-carbon nanotubes are replaced with hydroxyl-modified carbon nanotubes of the same mass, and the remaining steps, materials and compositions are consistent with those of Example 6, specifically including: 7 g of the hydroxyl-modified carbon nanotubes prepared in Example 4 were added to 90 g of the resin matrix prepared in Example 1, and then 3 g of Irgacure 819 were added, and the mixture was uniformly mixed by stirring and ultrasonication to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in a UV curing machine for 5 minutes to obtain a UV-curable antistatic coating.
[0054] Example 10 The only difference from Example 6 is that the silver-carbon nanotubes are replaced with copper powder of the same mass, and the remaining steps, materials and compositions are consistent with those of Example 6, specifically including: 7 g of the copper powder prepared in Example 5 was added to 90 g of the resin matrix prepared in Example 1, and then 3 g of Irgacure 819 was added, and the mixture was uniformly mixed by stirring and ultrasonication to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in a UV curing machine for 5 minutes to obtain a UV-curable antistatic coating.
[0055] Embodiment 11 The only difference from Example 6 is that the resin matrix is replaced by the resin matrix (shortened reaction time group), and the remaining steps and materials and compositions are consistent with Example 5, specifically including: 7 g of the silver-carbon nanotubes prepared in Example 3 were added to 90 g of the resin matrix prepared in Example 2 (shortened reaction time group), and then 3 g of Irgacure819 was added, and the mixture was uniformly mixed by stirring and ultrasonication to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in a UV curing machine for 5 min to obtain a UV-curable antistatic coating.
[0056] Comparative Example 1 The only difference from Example 6 is that no silver-carbon nanotubes are added, and the remaining steps, materials and compositions are consistent with those of Example 6, specifically including: 90 g of the resin matrix prepared in Example 1 was taken, 3 g of Irgacure 819 was added, and the mixture was uniformly mixed by stirring and ultrasonication to obtain an antistatic coating, which was cast into a film in a polytetrafluoroethylene template and cured in an ultraviolet curing machine for 5 minutes to obtain a UV-curable coating.
[0057] Performance Testing The UV-curable antistatic coatings prepared in Examples 6-11 and the coating prepared in Comparative Example 1 were subjected to resistivity tests respectively. The temperature in the test room was 25°C and the humidity was 20%. The surface resistivity of the antistatic coating was measured using a surface resistance tester. For the coating durability test, the prepared coating was placed in the test room and the resistivity of the coating was measured after 15 days and 30 days. For the coating stability test, the coating was heated to 70°C (humidity was 20%) and placed in a humidity of 80% (temperature was 25°C). The surface resistivity was measured using a surface resistance tester to compare the resistivity changes of the coating.
[0058] Table 1 Product performance test results of Examples 6-11 and Comparative Example 1: From the comparison of the data in the above table, we can see that: Compared with Example 6, the proportion of silver-carbon nanotubes is reduced in Example 7. Since the added amount is small, it is not easy for them to contact each other to form a conductive network, so the surface resistivity of the coating becomes higher, which decreases less than the group without adding antistatic agent (Comparative Example 1).
[0059] Compared with Example 6, the ratio of silver-carbon nanotubes is increased in Example 8, but its resistivity is increased compared with Example 6. This may be due to the excessive amount of antistatic agent added, which causes the silver-carbon nanotubes to agglomerate and micro-cracks in the coating; and the average change rate of the surface resistivity under the conditions of rising temperature and humidification increases significantly.
[0060] Compared with Example 6, in Example 9 and Example 10, the silver-carbon nanotubes are replaced by hydroxyl-modified carbon nanotubes and copper powder respectively. From the results, it can be seen that the antistatic properties of the two are slightly worse than that of the silver-carbon nanotubes. The reason is that the conductivity of the carbon nanotubes is greatly improved due to the modification of silver, but the coating prepared in Example 9 is better in terms of durability and stability. This is because the carbon nanotubes used are modified with concentrated nitric acid, so that their side walls and openings are oxidized, connected with hydroxyl groups, and then connected to the resin matrix by bonding, making it more stable. Copper powder and silver-carbon nanotubes are physically mixed in the resin matrix. The volume of copper powder is larger than that of silver-carbon nanotubes and its compatibility with resin is worse. Therefore, it is not easy to form a uniform antistatic network in the coating. In addition, as time goes by, conductive fillers are more likely to accumulate inside the coating and copper powder is oxidized. Therefore, the average change rate of durability is very high. When environmental factors change, such as temperature rise, the molecular movement inside the coating will intensify, and the copper powder will form more conductive channels inside the coating. When humidified, due to the effect of impurities in the water, the copper powder will make up for the lack of conductive network formed by the copper powder. Therefore, its stability changes dramatically, which leads to the durability and stability of the copper powder group being worse than that of the silver-carbon nanotube group.
[0061] Compared with Example 6, Example 11 uses a resin matrix with a shortened reaction time. Due to its insufficient reaction time, the reaction is incomplete, some monomers fail to react fully, the cross-linking density is low, the formed resin network is loose, and some microscopic defects are formed after the coating is cured. These defects will cause the conductive path to be incomplete and broken, resulting in a significant increase in the resistivity of the coating. When the temperature is high, the resin expands to fill the cracks and the resistivity will drop significantly. When humidified, water penetrates into it, and impurities in the water will also fill the conductive path, causing the resistivity to drop significantly.
[0062] Compared with Example 6, no antistatic agent was added to the coating of Comparative Example 1, and only the coating formed by the curing of the resin itself was used for resistivity testing. It was found that the resistance of the resin itself was very large and had no antistatic property.
[0063] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A UV curing antistatic coating, characterized in that: The method comprises the following raw materials in parts by weight: 85-95 parts of a resin matrix, 1-10 parts of an antistatic agent, and 3-5 parts of a photoinitiator; wherein: The resin matrix comprises the following raw materials in parts by weight: 30-40 parts of maleic anhydride, 30-40 parts of tetrahydrophthalic anhydride, 12-17 parts of ethylene glycol, 15-20 parts of propylene glycol, 3-5 parts of diluent, 0.5-2 parts of inhibitor, and 1-3 parts of production aid; The antistatic agent includes one or more of hydroxyl-modified carbon nanotubes, silver-carbon nanotubes and copper powder.
2. The UV curing antistatic coating according to claim 1, characterized in that: The diluent is selected from styrene, methacrylate fatty acid; The polymerization inhibitor is selected from methyl hydroquinone, p-benzoquinone, and hydroquinone; The production aids include leveling agents and / or defoaming agents.
3. A method for preparing the UV curing antistatic coating according to claim 1 or 2, characterized in that include: The antistatic agent is added into the resin matrix, mixed evenly, and the photoinitiator is added, mixed evenly to obtain the UV curing antistatic coating.
4. The preparation method according to claim 3, characterized in that: The preparation method of the resin matrix comprises: uniformly mixing ethylene glycol and propylene glycol, heating to 55-65° C., adding maleic anhydride, heating to 110-130° C., adding tetrahydrophthalic anhydride, heating to 170-190° C. and keeping the temperature for 1-3 hours, heating to 195-210° C. and keeping the temperature for 0.5-2 hours, cooling to 160-180° C., adding an inhibitor, cooling to 110-130° C., adding a diluent, producing an auxiliary agent, and obtaining the resin matrix.
5. The preparation method according to claim 3, characterized in that: The preparation method of the hydroxyl-modified carbon nanotubes comprises: adding 2-5 parts by weight of carbon nanotubes to 95-98 parts by weight of an acid-modified solution, stirring for reaction for 5-6 hours, and then ultrasonically dispersing at 60-70° C. for 15-25 hours to obtain the hydroxyl-modified carbon nanotubes.
6. The preparation method according to claim 3, characterized in that: The preparation method of the silver-carbon nanotubes comprises: adding 0.3-1 parts by weight of carbon nanotubes to 20-40 parts by weight of a composite strong oxidizing solution, stirring and reacting at 85-95° C. for 1-2 hours, washing with water, filtering with suction, drying and grinding after the reaction is completed; then adding 25-45 parts by weight of a composite modified solution, stirring and reacting at room temperature for 2-3 hours, washing with water, filtering with suction, drying and grinding after the reaction is completed; then placing the carbon nanotubes in 25-35 parts by weight of a silver ammonia solution, stirring and reacting for 0.5-1 hour, adding 3-7 parts by weight of glucose, continuing to stir and react for 2-3 hours, washing, filtering with suction, drying and grinding after the reaction is completed, so as to obtain the silver-carbon nanotubes.
7. The preparation method according to claim 6, characterized in that: The composite strong oxidizing solution is a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a mass ratio of (1.5-2.5):1; The composite modified solution is a mixed solution of stannous chloride solution and concentrated hydrochloric acid in a mass ratio of (0.5-1.5):1; the concentration of the stannous chloride solution is 0.3-0.7 g / L; The silver ammonia solution is ammonia water containing 3-7wt% silver nitrate.
8. The preparation method according to claim 4, characterized in that: The copper powder is pretreated: 20-25 parts by weight of copper powder is added to 35-55 parts by weight of modified solution, stirred for reaction for 1-2 hours, filtered, added to 40-55 parts by weight of purified solution, stirred for 10-20 minutes, filtered, and dried to obtain pretreated copper powder.
9. The preparation method according to claim 8, characterized in that: The modified solution is a mixed solution of anhydrous ethanol and concentrated hydrochloric acid in a mass ratio of (0.5-1.5):1; The purification solution is ether, anhydrous ethanol or isopropanol.
10. A method for using the UV curing antistatic coating according to claim 1 or 2, characterized in that include: The UV curing antistatic coating is applied on the surface of the substrate and UV cured to obtain the UV curing antistatic coating.
Citation Information
Patent Citations
Display device based on electrostatic protection
CN106189743A
O-phenyl type photo-curable unsaturated polyester resin and preparation method thereof
CN109180921A
Photocuring carbon-based conductive ink and preparation method thereof, immobilized enzyme conductive electrode and preparation method and application thereof
CN117106339A